Pengaruh Interest Based Income dan Fee Based Income Terhadap Return on Assets pada Perusahaan Perbankan yang Terdaftar di BEI Tahun 2019 - 2021 - Akhmal Firdhaus Ibnusolikhin; Nur Diana; M. Cholid Mawardi (e_Jurnal Ilmiah Riset Akuntansi, 2023)
Return on assets is an indicator to determine the ability of a company to gain overall profits. This is an important concern for a company in developing its business. Return on assets is effected by several variables including interest based income and fee based income. This research goals to determine and examine the effect of interest-based income and fee-based income on return on assets in banking organization listed on the Indonesia Stock Exchange in 2019-2021.The type of research used in this research is correlational research with a quantitative approach. Data collection techniques through secondary data in the form of financial reports. The sample collection technique used purposive sampling which obtained as many as 32 samples of banking organization listed on the Indonesia Stock Exchange. The data evaluation technique in this research is more than one linier regression evaluationThe results confirmed that interest based income had a positive and significant effect on return on assets, even as fee based income had a negative and significant effect on return on assets.Keywords: Interest based income, Fee based income, Return on assets.